Feasibility and Safety of Intra-Dialysis Yoga and Education in Maintenance Hemodialysis Patients - Birdee, Gurjeet S. (J Ren Nutr, 2015)
OBJECTIVE: Patients with end-stage renal disease on maintenance hemodialysis are much more sedentary than healthy individuals. The purpose of this study was to assess the feasibility and safety of a 12-week intra-dialysis yoga intervention versus a kidney education intervention on the promotion of physical activity. DESIGN AND METHODS: We randomized participants by dialysis shift to either 12-week intra-dialysis yoga or an educational intervention. Intra-dialysis yoga was provided by yoga teachers to participants while receiving hemodialysis. Participants receiving the 12-week educational intervention received a modification of a previously developed comprehensive educational program for patients with kidney disease (“Kidney School”). The primary outcome for this study was feasibility based on recruitment and adherence to the interventions, and safety of intra-dialysis yoga. Secondary outcomes were to determine the feasibility of administering questionnaires at baseline and 12-weeks including the Kidney Disease-Related Quality of Life-36. RESULTS: Among 56 eligible patients approached for the study, 55% (n=31) were interested and consented to participation with 18 assigned to intra-dialysis yoga and 13 to the educational program. A total of 5 participants withdrew from the pilot study, all from the intra-dialysis yoga group. Two of these participants reported no further interest in participation. Three withdrawn participants switched dialysis times and therefore could no longer receive intra-dialysis yoga. As a result, 72% (13 of 18) and 100% (13 of 13) of participants completed 12-week intra-dialysis yoga and educational programs, respectively. There were no adverse events related to intra-dialysis yoga. Intervention participants practiced yoga a median of 21 sessions (70% participation frequency), with 60% of participants practicing at least 2 times a week. Participants in the educational program completed a median of 30 sessions (83% participation frequency). Of participants who completed the study (n=26), baseline and 12-week questionnaires were obtained from 85%. CONCLUSIONS: Our pilot study of a 12-week intra-dialysis yoga and 12-week educational intervention reached recruitment goals, but less than targeted completion and adherence to intervention rates. This study provided valuable feasibility data to increase follow-up and adherence for future clinical trials to compare efficacy.